Bioaccumulation of polycyclic aromatic hydrocarbons by arctic and temperate benthic species. (27th February 2019) - Szczybelski, Ariadna S.; Diepens, Noël J.; van den Heuvel‐Greve, Martine J.; van den Brink, Nico W.; Koelmans, Albert A.
Abstract: Increasing oil and gas activities may substantially increase chemical stress to benthic ecosystems in the Arctic, and it is necessary to evaluate such environmental risks in these systems. Risk assessment procedures for oil‐related compounds (e.g., polycyclic aromatic hydrocarbons [PAHs]) should address differences in exposure between Arctic and temperate benthos. We compare for the first time the bioaccumulation of PAHs by Arctic benthic invertebrate species with that of temperate species, based on their biota–sediment accumulation factors (BSAFs). Measured PAH BSAFs were generally higher in temperate bivalves ( Limecola balthica ) than in Arctic bivalves ( Macoma calcarea ), whereas BSAFs in Arctic polychaetes ( Nephtys ciliata ) were higher than in temperate polychaetes ( Alitta virens ). Differences in measured BSAFs were explained by species‐specific feeding modes and traits. However, modeled BSAFs revealed that steady state was not likely to be reached in the 28‐d tests for all PAHs and organisms. Due to the low numbers of individuals, most species‐specific parameters were too uncertain to reveal differences between Arctic and temperate species. The results of the present study suggest that data from temperate species could be used as a surrogate for Arctic species in risk assessment. Environ Toxicol Chem 2019;38:883–895. © 2019 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.